2004
DOI: 10.1254/jphs.94.313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sasanquasaponin on Ischemia and Reperfusion Injury in Mouse Hearts

Abstract: Abstract. We investigated effects of sasanquasaponin (SQS), a traditional Chinese herb's effective component, on ischemia and reperfusion injury in mouse hearts and the possible role of intracellular Cl -homeostasis on SQS's protective effects during ischemia and reperfusion. An in vivo experimental ischemia model was made in mice (weight 27 -45 g) using ligation of left anterior descending coronary artery, and in vitro models were made in perfused hearts by stopping flow or in isolated ventricular myocytes by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 34 publications
(21 reference statements)
2
39
0
Order By: Relevance
“…Previous studies by our group showed that SQS effectively protected against myocardial injury in an isoproterenol-induced rat model of ischemia in vivo and in a hypoxia and reoxygenation model in Langendorff-perfused rat hearts in vitro (8,22,23). Another previous study by our group revealed that SQS exerts its cardioprotective effects by suppressing intracellular Cl -accumulation induced by sI/R (9).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Previous studies by our group showed that SQS effectively protected against myocardial injury in an isoproterenol-induced rat model of ischemia in vivo and in a hypoxia and reoxygenation model in Langendorff-perfused rat hearts in vitro (8,22,23). Another previous study by our group revealed that SQS exerts its cardioprotective effects by suppressing intracellular Cl -accumulation induced by sI/R (9).…”
Section: Discussionmentioning
confidence: 88%
“…The neonatal primary rat cardiomyocytes were divided into various experimental groups as follows: i) In the control group, cardiomyocytes were incubated under normal conditions for an additional 24 h; ii) in the sI/R group, cardiomyocytes were subjected to anoxia by incubating them in fresh anoxic medium [0.9 mM NaH 2 PO 4 , 6.0 mM NaHCO 3 , 1.8 mM CaCl 2 , 1.2 mM MgSO 4 , 40 mM sodium lactate, 20 mM 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES), 98.5 mM NaCl, 10.0 mM KCl, pH 6.8; Sigma-Aldrich] at 37˚C in a chamber containing 95% N 2 and 5% CO 2 for 3 h. Subsequently, the medium was replaced with re-oxygenation medium (129.5 mM NaCl, 5.0 mM KCl, 0.9 mM NaH 2 PO 4 , 20 mM NaHCO 3 , 1.8 mM CaCl 2 , 1.2 mM MgSO 4 , 5.5 mM glucose, 20 mM HEPES, pH 7.4; Sigma-Aldrich) and the cells were incubated at 37˚C in an atmosphere of 95% air and 5% CO 2 for 2 h; iii) In the SQS+sI/R group, cells were pre-treated with SQS at 10 µM for 24 h prior to sI/R; iv) In the SQS+εV1-2+sI/R group, cells were pre-treated with εV1-2 (1 µM) and SQS (10 µM) for 24 h prior to sI/R. The doses of SQS and εV1-2 used were selected on the basis of a preliminary study by our group and previous reports (8,18,19).…”
Section: Reagents Sqs Was Kindly Provided By Professor Yongmingmentioning
confidence: 99%
See 2 more Smart Citations
“…Sasanquasaponin (37) inhibited ischemic/reperfusion-induced cardiac arrhythmias by modulating intracellular Cl À homeostasis in mouse hearts [48]. Saponin 37 protected cardiomyocytes against oxidative stress induced by anoxia-reoxygenation by attenuating reactive oxygen species generation and increasing activities of endogenous antioxidants [49].…”
mentioning
confidence: 99%